(untitled) (Security Dialogues, 2023)
The scientific paper explores women as perpetrators of criminal acts andtheir penal treatment, providing insights into the specifics and challenges they faceduring incarceration. Traditionally, prisons were primarily oriented towards men, buttoday there are specific prison units and facilities exclusively for female inmates. In the introduction, we address the history and development of the prison system forwomen, including the creation of specialized units and a gender-sensitive approachto imprisonment. The second part investigates the specifics of women’s incarceration,including healthcare needs, education, vocational training, challenges of motherhoodand childcare in prison, as well as psychological aspects of women’s imprisonment. The third part examines the issues and challenges women encounter during incarceration,such as prison system overcrowding, gender discrimination, and violence againstwomen in prison. Additionally, we explore the application of alternative punishmentmeasures for women, including home confinement, rehabilitation and reintegrationprograms, and harm reduction measures for women with special needs.